Learning Media for Sound Picture Cards Based on E-Flashcard Quizlet Content for Elementary School IPAS Lessons - Oktaviani, Putri; Isdaryanti, Barokah (Journal of Education Technology, 2023)
Some schools can make maximum use of technology. The lack of adapting learning media to technological developments impacts students who do not benefit from technology to the maximum. This research aims to develop Quizlet-based Flashcard electronic learning media for science and science learning for class V elementary school. Research and development were carried out using the ADDIE development model. Data collection methods through interviews, questionnaires and tests. Data collection instruments are in the form of questionnaires and test questions. The subjects of this research were 1 subject matter expert and 1 learning media expert. The product implementation or trial was carried out in two stages, namely a small-scale trial of 6 students and a large-scale trial of 27 students. The techniques used to analyze data are qualitative descriptive analysis, quantitative and inferential statistics. The results of the research are that the media developed received very decent qualifications from material experts and learning media experts. The t-test results show a significant increase in the pre-test and post-test results. The N-Gain test results show an increase in the high category. It was concluded that Quizlet-based E-Flashcard learning media effectively improved student learning outcomes. The implication of this research is that the E-Flashcard Quizlet-based Sound Picture Card media that has been developed can be used as a solution to help students learn science subjects and also make it easier for teachers in teaching and learning activities.